Validation of an Accelerated Aging Protocol for Microencapsulated Mustard Oil in Emulsion - Muneratto, Vítor Mathias [UNESP]; Maia, Nilson Borlina; Gonçalves, José Roberto Tibúrcio; Nicoletti, Vânia Regina [UNESP]; Moser, Poliana [UNESP] (ASTM International, 2025)
Allyl isothiocyanate (AITC) is the main compound found in mustard oil. Despite exhibiting important properties, such as antibacterial and antifungal effects, AITC has a volatile nature that can shorten its action time. Encapsulating emulsions present a viable solution for preserving the integrity of AITC, facilitating its effective application, and extending its shelf life. In this context, accelerated aging tests serve as valuable tools for predicting product behavior based on tests that can be carried out over shorter periods. The present study aimed to validate the ASTM F1980-21, Standard Guide for Accelerated Aging of Sterile Barrier Systems and Medical Devices, accelerated aging protocol for emulsions encapsulating mustard oil. Two emulsions were produced using bilayer technique, named E1/20 and E2/46, containing 20 % and 46 % mustard oil, respectively. The aqueous and oil phase separation levels as well as the average droplet size were selected to assist in analyzing the stability behavior. Mustard oil emulsions were subjected to stability tests at three different temperatures (room temperature, 35°C, and 45°C). The first test represented a real-time aging study (shelf life study), whereas the other two represented accelerated aging tests. Real-time and accelerated aging data were correlated using the accelerated aging factor and the aging factor (Q10). The formulation E1/20 was stable for a shorter time compared with E2/46 (breakpoint at day 240 versus day 410), despite exhibiting smaller droplets (3.82 versus 7.38 μm) and a longer delay in the onset of instability (first structural alteration observed at day 180 compared with day 60). The protocol generated satisfactory Q10 values for both emulsions, approximately 1.8 for E1/20 and 2 for E2/46, enabling the accelerated aging of the emulsions by 3.2 and 4.2 times, respectively, when exposed to 45°C. Thus, this validates the protocol for these emulsions.
Keywords: accelerated aging; ASTM F1980-21 protocol; bilayer emulsion; microencapsulation; mustard oil; shelf life; stability